THE THE IMPLEMENTATION OF DISCOVERY LEARNING ON THE MUSIC ARTS SUBJECT AT SENIOR HIGH SCHOOL - Riski T. R. Lamansiang; R.A.Dinar Sri Hartati; Meyny Kaunang (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The challenge addressed by this research is how to integrate the Discovery Learning framework for teaching music arts into conventional classroom settings. This study used a descriptive qualitative research strategy and SMA Katolik Karitas Tomohon is the research location. Lucky Mongi S.Pd., a music art teacher at SMA Katolik Karitas Tomohon for the last decade, and the students of his Music arts class were the subject of this research. After analyzing information gathered via observation, interviews, and written records, the usefulness of the learning model Discovery Learning is clear. The music instructor at SMA Katolik Karitas Tomohon, grade XA, has adopted the appropriate stages from the Discovery Learning curriculum to pique the pupils' curiosity about the topic at hand: the form and value of musical notes. In order to make the learning process more meaningful and to make students comfortable and not bored during the teaching and learning process, researchers found that most students are actively involved in asking questions about the material delivered by music teachers in the process of teaching and learning activities in class. The result is that the learning strategy used at SMA Katolik Karitas Tomohon to facilitate the study of music is appropriate.